Duration of Second Stage of Labor and Birth Canal Tears in Mothers Who Do Pregnancy Exercises - Rani Marlida Nurbaeti; Arih Diyaning Intisari Intisari; Budi Aji (Green Publisher Indonesia, 2025)
Childbirth is considered a frightening experience, even some women who get traumatized and did not dare to get pregnant again. Whereas many ways and the invention of the experts on behalf of the mothers in childbirth, including pregnancy exercise. The purpose of this study to determine the relationship of the duration of the second stage of labor and birth canal laceration in women who are pregnant do gymnastics in BPM Ny. E Tasikmalaya in 2022. This type of research is kolerasional a study that examined two variables simultaneously by using cross sectional research that studied the pregnancy exercises of the correlation between the risk factors to the effects of the approach, observation or data collection at once. The population in this study were all women giving birth in BPM Ny. E city tasikmalaya in January-July. Sampling using total sampling technique in order to obtain a sample of 32 people. Retrieving data using questionnaires then the data were analyzed using chi-square statistical test. The survey results revealed that the duration of labor relations kala There ll on women who undergo pregnancy exercise (ρ value = 0.001 at α = 0.05), no association rips the birth in women who are pregnant do gymnastics (ρ value = 0.000 at α = 0 , 05). It is expected that all pregnant women, especially pregnant women who are in the scope of BPM Ny. E apply existing theories in this research that is routinely doing pregnancy exercise to prepare for childbirth.